Race, Gender and the Kobe Bryant (or O.J. Simpson) Case - Markovitz, Jonathan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
I often devote a week of my course on popular culture to the Kobe Bryant case (with some modification, the lesson plan could focus on the O.J. Simpson case instead). I teach the class as a lecture/discussion session. I contextualize the case by focusing on histories of lynching, interracial rape, and the anti-rape movement. The central issue for the course is to think about the ways that contemporary audiences make sense of unfolding racial spectacles, and, more specifically, to examine the role that collective memories of past racial spectacles may play in this process. We’re ultimately interested in examining the impact of the case for national processes of racial formation.